Tinjauan Kondisi Fisik Atlet Bolabasket - Hendri Mulyadi; Badri Nikon (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
This study aims to find out how well the physical conditions possessed by basketball athletes at SMK Negeri 1 Pulau Punjung that are related to endurance, strength, speed, agility and explosive strength of limb muscles. This type of research is a descriptive study. The population in this study were 37 basketball athletes from SMK Negeri 1 Punjung Island. Sampling was done by Purposive Sampling, then the sample amounted to 25 people. After the data is obtained, the data analysis technique in this study uses frequency tabulation. The results of this study indicate: 1) a dominant review of durability possessed by basketball athletes at SMK Negeri 1 Punjung Island is 10.59 - 13.25 classified as good category (60%), 2) review of the dominant strength possessed by basketball athletes at SMK Negeri 1 Punjung Island is 57.50 - 78.00 classified as medium category (64%), 3) review of the dominant speed possessed by basketball athletes at SMK Negeri 1 Pulau Punjung is 4.97 - 5.40 classified as medium category (32%), 4) agility review the dominant possession of basketball athletes at Pulau Punjung State Vocational High School 1 was 14.10-15.74 classified as medium category (14%), 5) review of leg muscles explosive power dominantly owned by basketball athletes in Pulau Punjung State Vocational High School was 31-38 classified as medium (72%). Keywords: Physical Condition, Basketball Athletes.